Responsabilidades do auditor nos eventos subsequentes - Silva, Vítor Daniel Mota da (2021)
Identifying the nature of an event, the need to adjust it in the financial statements or its disclosure, is a function of the entity and auditors must give their opinion. In auditing, due to the consequences that an event can cause on the financial statements and on the issuance of the audit opinion, this issue must be carefully analyzed by the auditors, in order to demonstrate objective, reliable and clear information to the users of the financial statements. In this dissertation the main objective is to analyze and describe the audit of subsequent events. To achieve this, it will be performed a Literature Review, Legal Framework and approach the most important theoretical concepts in order to understand how such concepts apply in the auditing profession. In the empirical study a quantitative analysis will be carried out through the use of a survey, which was directed to Auditors, Chartered Accountants and Professors in order to obtain the results to give answers to the formulated hypotheses. Thus, through the empirical study, it was possible to conclude that the causes and consequences of subsequent events are relevant in issuing the audit opinion; the development of the audit work must include the analysis of subsequent events; and to understand the events it is essential to know the environment in which the entity's business is inserted.